Hepatitis B treatment eligibility in West Africa: Uncertainties and need for prospective cohort studies - Jaquet, Antoine; Nouaman, Marcellin; Tine, Judicaël; Tanon, Aristophane; Anoma, Camille; Inwoley, André; Attia, Alain; Ekouevi, Didier K.; Seydi, Moussa; Dabis, François; Wandeler, Gilles (Liver international, 2017)
Background & Aims While universal screening of hepatitis B virus (HBV) is recommended in high burden countries, little is known about the proportion of HBV‐infected persons in need of antiviral therapy in these settings. Methods Prisoners in Senegal and Togo as well as female sex workers and men who have sex with men in Cote d'Ivoire were screened for HBV infection. All HBsAg‐positive participants underwent transient elastography, alanine aminotransferase (ALT) and HBV viral load (VL) quantification. Individuals with cirrhosis or those aged >30 years with an HBV replication ≥20 000 IU/mL and elevated ALT were considered eligible for antiviral therapy. Results Of 1256 participants, 110 (8.8%) were HBsAg positive; their median age was 30 years [interquartile range: 25‐33] and 96 (86.5%) were men. Three individuals (2.7%) had cirrhosis, while 28 (29.5%) of 94 participants with available measurements had an HBV VL ≥20 000 IU/mL. Overall, 11 (10.0%) subjects were considered eligible for immediate antiviral treatment (2.1% of participants in Dakar, 7.7% in Abidjan and 21.6% in Lome, P=.001) and 59 (53.4%) for close monitoring due to the presence of significant liver fibrosis, elevated ALT or significant HBV replication. Conclusions Among vulnerable populations in West Africa, a minority of HBV‐infected individuals were eligible for immediate antiviral therapy. Prospective cohort studies are necessary to evaluate anti‐HBV treatment eligibility facing the significant proportion of individuals with active chronic HBV infection.